2001
DOI: 10.1002/1521-396x(200111)188:1<47::aid-pssa47>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

A Band-Tail Model for InGaN Alloy System and Design for Quantum Well Laser Operation

Abstract: We have constructed a new theoretical model of compositional fluctuation in InGaN quantum wells (QWs) to investigate the effects of the fluctuation on emission properties and laser performance. The temperature dependence of the photoluminescence decay time for InGaN-QW structures is fully analysed by the model in terms of a band-edge state modified by the compositional variation. This model is then used to predict performance for InGaN-QW lasers. We found that the differential gain and the critical carrier den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the calculation, the dispersion of conduction band was assumed as parabolic, and In-compositional fluctuation was considered based on the Fermi-level constant model. [33][34][35][36] Figure 8 show calculated (a) maximum optical gain and (b) threshold carrier density as functions of substrate orientation angle (θ) for green-lightemitting In 0.3 Ga 0.7 N QWs with 2 nm well width. It can be seen that higher optical gain and lower threshold carrier density are obtained for E//X 1 polarization for nonpolar orientation.…”
Section: Resultsmentioning
confidence: 99%
“…In the calculation, the dispersion of conduction band was assumed as parabolic, and In-compositional fluctuation was considered based on the Fermi-level constant model. [33][34][35][36] Figure 8 show calculated (a) maximum optical gain and (b) threshold carrier density as functions of substrate orientation angle (θ) for green-lightemitting In 0.3 Ga 0.7 N QWs with 2 nm well width. It can be seen that higher optical gain and lower threshold carrier density are obtained for E//X 1 polarization for nonpolar orientation.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of the theoretical model is basically the same as that of our previous model. [5][6][7]23,25) It is assumed in the model that both the conduction and valence bands are parabolic, and that the bandgap energy varies spatially by the Gaussian distribution function with standard deviation σ. We also assumed that the quasi-Fermi energy is spatially uniform throughout the QW layer, which means that the scale of fluctuation is within the carrier diffusion length.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…In our study, we have theoretically investigated the effects of the potential fluctuation on the lasing characteristics under our fluctuation model 6,23) and have found that the temperature dependence of the lasing threshold is strongly affected by the degree of fluctuation. In addition, optical-pump stimulatedemission measurements have been performed for an epi-layer sample with an InGaN-QW laser diode structure, and the theoretically predicted phenomena have been observed in the measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The energy distribution of electrons and holes can be calculated from the product of the DOS and Fermi-Dirac distribution functions when both the quasi-Femi levels for electrons and holes are assumed as spatially uniform. 21) Then, the spontaneous emission spectra are calculated under the k-selection rule by assuming that the transition probabilities are simply proportional to the product of electron and hole densities. Figure 5 shows an example of a calculated emission spectrum, which is similar to the spectrum shown in Fig.…”
Section: Theoretical Modelmentioning
confidence: 99%